(untitled) (Al-Qamar, 2024)
When the Almighty Allah adorned this earthly realm with humankind, the eternal struggle between good and evil also came into existence. As humanity became increasingly entangled in the abyss of misguidance, the Supreme Guide—Allah, the Most Glorious, continued to send His chosen messengers to illuminate the path from darkness to light. While some individuals embraced the truth, others outright denied it. However, there were also those who wavered in between. Regarding such people, Allah Almighty states in Surah An-Nisa: "They are wavering between this and that, belonging neither to these nor to those. And whoever Allah leaves astray, you will never find for him a way." (Surah An-Nisa: 143) Furthermore, Allah has also identified individuals who selectively accept only what aligns with their own desires while rejecting what contradicts their inclinations. Almighty Allah has not only highlighted their motives but has also recorded their statements: “They wish to make a distinction between Allah and His Messenger and say, ‘We believe in some and reject others,’ and they seek to get a way in between." (Surah An-Nisa: 150) The disbelievers of Hadith adopt a similar approach, attempting to carve out a middle path within Islam by claiming adherence to the Quran while simultaneously rejecting the teachings of the Prophet (ﷺ), thereby altering the religion according to their own desires. By His perfect wisdom, Allah ensured that nearly all His prophets were first accepted and trusted by their societies. He supported them with miracles so that the people would recognize their truthfulness and develop unwavering confidence in their character. This foundational trust enabled the followers to fully submit to and obey the divine instructions conveyed by the prophets. Consequently, how the early Muslim community was guided towards righteousness and the straight path remains the most effective method even today that is, the complete obedience and adherence to the teachings of the Prophet (ﷺ). While we do not claim to have examined every single Hadith compilation, we have yet to come across any authentic narration or Quranic verse that negates the acceptance of Hadith. However, the disbelievers of Hadith present certain objections aimed at discrediting the Hadith corpus. When subjected to rigorous academic scrutiny, these objections appear to stem from individuals who are heavily influenced by foreign ideologies, parrot the arguments of outsiders, interpret the Quran as per their whims, and are disconnected from the mainstream Muslim scholarship. These individuals, numbering no more than 15 to 20 persons across the entire 1,500-year history of Islam, attempt to impose their personal opinions upon the entire Ummah. Ironically, their objections are often borrowed from the works of Orientalists, who have historically sought to undermine Islam. The weight of their argument’s pales in comparison to the immense intellectual legacy of Islam. This article, therefore, presents a comprehensive scholarly analysis of their objections. Each objection will be systematically listed, attributed to its proponent, and then critically examined. This analytical process will clearly demonstrate the credibility of their claims and the strength of the responses to them. Ultimately, this discourse will determine whether their arguments hold any significant weight and whether the necessity of Hadith remains indispensable to Islam.